2022
DOI: 10.1093/pnasnexus/pgac065
|View full text |Cite
|
Sign up to set email alerts
|

Deep-learning microscopy image reconstruction with quality control reveals second-scale rearrangements in RNA polymerase II clusters

Abstract: Fluorescence microscopy, a central tool of biological research, is subject to inherent trade-offs in experiment design. For instance, image acquisition speed can only be increased in exchange for a lowered signal quality, or for an increased rate of photo-damage to the specimen. Computational denoising can recover some loss of signal, extending the trade-off margin for high-speed imaging. Recently proposed denoising on the basis of neural networks shows exceptional performance but raises concerns of errors typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Size-control by amphiphiles can be seen in several biological example cases. A particularly well-studied case is the compartmentalization of transcription inside of the cell nucleus. One prominent example is RNA polymerase II (Pol II), the enzyme complex responsible for transcribing most eukaryotic genes, which acts as a bivalent connecting particle between microphase-separated domains enriched in either DNA or RNA. An amphiphilic effect of ongoing transcription can also be seen by super-resolution microscopy of clusters of transcriptional machinery in stem cells. , These clusters form by a phase-separation mechanism and unfold or even split into smaller clusters when they are engaged by genes that undergo transcriptional activation. , This effect can be reproduced in detail by a polymer model, in which transcribed genes are described as amphiphiles that associate with transcriptional clusters that, in turn, form by a liquid condensation mechanism . Here, we extend the synthetic DNA-nanomotif droplet platform by amphiphile-motifs and show that the effect of these amphiphile-motifs closely resembles key features of the dispersal of embryonic transcriptional clusters.…”
Section: Dispersal Of Rna Polymerase II Clusters By An Amphiphilic Ef...mentioning
confidence: 99%
See 2 more Smart Citations
“…Size-control by amphiphiles can be seen in several biological example cases. A particularly well-studied case is the compartmentalization of transcription inside of the cell nucleus. One prominent example is RNA polymerase II (Pol II), the enzyme complex responsible for transcribing most eukaryotic genes, which acts as a bivalent connecting particle between microphase-separated domains enriched in either DNA or RNA. An amphiphilic effect of ongoing transcription can also be seen by super-resolution microscopy of clusters of transcriptional machinery in stem cells. , These clusters form by a phase-separation mechanism and unfold or even split into smaller clusters when they are engaged by genes that undergo transcriptional activation. , This effect can be reproduced in detail by a polymer model, in which transcribed genes are described as amphiphiles that associate with transcriptional clusters that, in turn, form by a liquid condensation mechanism . Here, we extend the synthetic DNA-nanomotif droplet platform by amphiphile-motifs and show that the effect of these amphiphile-motifs closely resembles key features of the dispersal of embryonic transcriptional clusters.…”
Section: Dispersal Of Rna Polymerase II Clusters By An Amphiphilic Ef...mentioning
confidence: 99%
“…To allow for the comparison of the effect of DNA-based amphiphiles against a biological model system, we first characterize how transcriptional clusters are affected by the amphiphilic effects exerted by the transcribed genes. In the zebrafish embryo, for a number of genes, transient visits to especially long-lived and prominent transcriptional clusters occur, which are tightly coupled with the transcriptional control of these genes by so-called “super-enhancers”. ,, As genes engage with transcriptional clusters and transcript elongation begins, transcriptional clusters unfold or even split into multiple parts (Figure A). This effect has been attributed to an amphiphilic property of genes that undergo activation in association with these prominent transcriptional clusters: while these genes exhibit an increased tendency to associate with transcriptional clusters, the beginning of transcript elongation additionally drives the exclusion of these genes from the transcriptional cluster …”
Section: Dispersal Of Rna Polymerase II Clusters By An Amphiphilic Ef...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors performed Monte Carlo simulations to explain the experimentally observed microphase separation. In subsequent studies ( Pancholi et al, 2021 ; Hajiabadi et al, 2022 ), it was shown that RNA Pol II exhibit different types of organization depending on its phosphorylation state and interactions with active genes. Our findings complement these previous studies by showing experimental evidence of a robust core-shell organization of chromatin and RNA Pol II.…”
Section: Introductionmentioning
confidence: 99%
“…The authors performed Monte Carlo simulations to explain the experimentally observed microphase separation. In subsequent studies [43,44], it was shown that RNA Pol II exhibit different types of organization depending on its phosphorylation state and interactions with active genes. Our findings complement these previous studies by showing experimental evidence of a robust core-shell organization of chromatin and RNA Pol II.…”
Section: Introductionmentioning
confidence: 99%